2005
DOI: 10.1186/1471-2334-5-60
|View full text |Cite
|
Sign up to set email alerts
|

Kocuria kristinae infection associated with acute cholecystitis

Abstract: Background: Kocuria, previously classified into the genus of Micrococcus, is commonly found on human skin. Two species, K. rosea and K. kristinae, are etiologically associated with catheter-related bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 20 publications
1
67
0
2
Order By: Relevance
“…Studies have suggested a relation between the use of antimicrobial agents in livestock animals and in emergence pathogens of human with a decreased in the susceptibility or completely resistance to antibiotics (Schjørring and Krogfelt, 2011;Landers et al, 2012;Santos, 2010). High levels of multiple resistance represent a potential risk to human health and can difficult the treatment of diseases in animals and humans, exacerbating the curable clinical cases (Ma et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested a relation between the use of antimicrobial agents in livestock animals and in emergence pathogens of human with a decreased in the susceptibility or completely resistance to antibiotics (Schjørring and Krogfelt, 2011;Landers et al, 2012;Santos, 2010). High levels of multiple resistance represent a potential risk to human health and can difficult the treatment of diseases in animals and humans, exacerbating the curable clinical cases (Ma et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although these bacteria may be considered as environmental, being found in soil and water systems, they may be potentially pathogenic in susceptible individuals. Case reports have shown infectivity by several of these bacteria, but they are generally catheter-related bacteraemias 23,24 or infections in immunocompromised individuals 25 , with one report of fatal infection 26 . The actual risk these organisms pose to technicians or patients is unknown, but reducing the risk of potentially infective solutions would be advisable.…”
Section: Discussionmentioning
confidence: 99%
“…The potential pathogenicity of these organisms is unknown from contamination of removable orthodontic appliances, but has been shown to be infective in susceptible, immunocompromised patients. However, this is generally related to invasive medical treatment, indwelling urinary catheters 23 or central venous catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Kocuria is a member of the Micrococcaceae family, which presently comprises 18 species [3]. Although generally regarded as harmless saprophytes that inhabit or colonize skin and oropharynx mucosa this aerobic, non-encapsulated, nonmotile bacteria can cause opportunistic infection in the immunocompromised host [3].…”
Section: Discussionmentioning
confidence: 99%